Pengaruh Terapi Akupresur Terhadap Intensitas Nyeri Persalinan - Siti Rofi’ah; Siti Chunaeni; Maryam (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: Pain in labor is a physiological thing as a result of the contraction of the uterine muscle. Acupressure is one of the techniques to reduce pain in labour.Objective: This research was to know the effectiveness of accupressure therapy toward pain intensity first stage of labor in primipara active phase I at Public Health Care Sumpiuh II, Banyumas District in 2013.Method: Type of the research was Pre experimental with one group pretest-postest design. The population was 30 maternals primipara active phase of the first stage. The sample used was total sampling.Result: before getting accupressure therapy, the majority of respondents were in severe pain category, after getting therapy, mostly in moderate pain category. There was the effect of acupressure therapy on pain intensity of active phase of the first stage of labor in primipara at Public Health Care II Sumpiuh Banyumas in 2013 with p value of 0.0001.Suggestion: Mom will be expected to receive maternity acupressure therapy in labor proccess. Suggesting for midwives to follow accupressure training and applicate that therapy to maternity. By applying that therapy in labor proccess is expected to reduce pain during labor in accordance to give new and excite experience for maternity.Keywords: acupressure, labor pain, primipara